2018
DOI: 10.15405/epsbs.2018.07.6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive And Regulatory Foundations Of Tolerance In Schoolchildren In Inclusive Education

Abstract: This article presents the results of an empirical study of tolerance as a systemic socio-psychological quality of personality. The aim of the work was to study the cognitive and regulatory foundations for the formation of schoolchildren's tolerance in the context of inclusive education. Tolerance was considered by us as a systemic formation of components. The cognitive component was studied on the basis of a cognitivestyle approach. The regulatory component was identified through the establishment of types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…The results demonstrated that self-regulation was the sole predictor of resilience. Moreover, it was found that self-regulation positively predicted academic achievement, whereas attachment avoidance negatively impacted it [12]. In a different study conducted by Korhan et Thus, both cognitive exibility and self-regulation play a substantial role in moderating examination anxiety among young individuals [13].…”
Section: Introductionmentioning
confidence: 93%
“…The results demonstrated that self-regulation was the sole predictor of resilience. Moreover, it was found that self-regulation positively predicted academic achievement, whereas attachment avoidance negatively impacted it [12]. In a different study conducted by Korhan et Thus, both cognitive exibility and self-regulation play a substantial role in moderating examination anxiety among young individuals [13].…”
Section: Introductionmentioning
confidence: 93%
“…Именно такой человек -толерантная личность -должен стать главным действующим лицом позитивного сценария развития человечества в современном мире. Формирование толерантной личности в подростке возможно через отработку жизненно необходимых социальных навыков, которые позволят подростку осваивать трудное искусство жить в мире и согласии с собой и с другими [3,9]. На занятиях мы создали для школьников условия для многократной отработки и привития таких навыков, как позитивного взаимодействия, решения конфликтных ситуаций, корректировки самооценки, самоутверждения, самопознания [6,8].…”
Section: рис 3 величины общего индекса толерантности в контрольной unclassified
“…Развитие личности способствует проявлению толерантности [9], поскольку черты зрелой личности включают в себя ориентацию на общечеловеческие ценности, креативность, независимость суждений, уважительное отношение к чужой точке зрения, стремление способствовать развитию других людей. Таким образом, формирование толерантности может пониматься нами, как программа развития личности.…”
Section: рис 4 величины общего индекса агрессивности в экспериментаunclassified